Efforts to Improve Children's Listening Skills through the Chain Whispering Play Method at RA PUI Sindangwargi - Gaosah, Ia; Jumiatun, Hillal (MANDAILING GLOBAL EDUKASIA, 2025)
This research is based on the results of the researcher's observations about the low ability of children to listen. One of the causes of this condition is that teachers still do not provide enough stimulation of listening activities and language development learning is still dominated by the role of the teacher. As a result, the classroom atmosphere is monotonous, passive and boring. In line with this problem, efforts were made to improve the listening skills of early childhood through the method of playing whispering in chains. This study aims to determine the planning, implementation, and improvement through the methods used. This research was conducted using Classroom Action Research with a two-cycle improvement implementation procedure. The subjects of the study were 20 group A students, consisting of 5 boys and 15 girls with student characteristics who have different abilities and potentials. Based on the results of the study and the results of data analysis, it can be concluded that there was a significant increase in children's listening skills from 10% before the improvement was carried out in cycles 1 and 2, to 50% in cycle 1 and 95% in cycle 2, which means that through the method of playing whispering in chains, listening skills can be improved in group A at RA PUI Sindangwargi.